The Mediation Effects of Fear on the Relationship between Gain/Loss Message Frames and Cognitive/Conative Responses - Shin, Sumin; Park, Sanghee; Ki, Eyun-Jung (Journal of Intelligent Communication, 2022)
This study investigates the underlying mechanism of fear appeal effects on behavioral changes applying the emotions-as-frame model and protection motivation theory to the green advertising context. The results indicate that a loss-framed message arises fear increasing severity, vulnerability, response efficacy, and self-efficacy, which in turn affect the intention to purchase a green product. Furthermore, this study results that a gain frame is more effective to lead green behavior than a loss frame.